Improving the performance of acoustic invisibility with multilayer structure based on scattering analysis - 蔡琛 袁樱 阚威威 杨京 邹欣晔 (Chinese physics B, 2016)
In this paper, acoustic scattering from the system comprised of a cloaked object and the multilayer cloak with only one single pair of isotropic media is analyzed with a recursive numerical method. The designed acoustic parameters of the isotropic cloak media are assumed to be single-negative, and the resulting cloak can reduce acoustic scattering from an acoustic sensor while allowing it to receive external information. Several factors that may influence the performance of the cloak, including the number of layers and the acoustic dissipation of the medium are fully analyzed. Furthermore, the possibility of achieving acoustic invisibility with positive acoustic parameters is proposed by searching the optimum value in the parameter space and minimizing the scattering cross-section.